Depletion of alveolar macrophages attenuates hypoxic pulmonary hypertension but not hypoxia-induced increase in serum concentration of MCP-1 - Žaloudíková, M; Vytášek, R; Vajnerová, O; Hniličková, O; Vízek, M; Hampl, V; Herget, J (Physiological research, 2016)
Exposure to hypoxia, leading to hypoxic pulmonary hypertension (HPH), is associated with activation of alveolar macrophages (AM). However, it remains unclear how AM participate in this process. There are studies which imply that the AM product monocyte chemoattractant protein-1 (MCP-1) plays an important role. Thus we tested: 1. if the selective elimination of AM attenuates HPH in rats, 2. the correlation of MCP-1 plasmatic concentrations with the presence and absence of AM during exposure to hypoxia, 3. the direct influence of hypoxia on MCP-1 production in isolated AM. We found that experimental depletion of AM attenuated the chronic hypoxia-induced increase in mean pulmonary arterial pressure, but did not affect the serum MCP-1 concentrations. Furthermore, the MCP-1 production by AM in vitro was unaffected by hypoxia. Thus we conclude that AM play a significant role in the mechanism of HPH, but MCP-1 release from these cells is most likely not involved in this process. The increase of MCP-1 accompanying the development of HPH probably originates from other sources than AM.
Keywords: potkani Wistar; Clodronic Acid; hypoxie; Macrophages, Alveolar; Animals; plicní hypertenze; Hypertension, Pulmonary; mužské pohlaví; Hypoxia; Male; Rats, Wistar; dichlormethylendifosfonát; Chemokine CCL2; zvířata; alveolární makrofágy; chemokin CCL2